Home-Based Tele-Exercise in Musculoskeletal Conditions and Chronic Disease: A Literature Review - Amorese, Adam J.; Ryan, Alice S. (Frontiers in Rehabilitation Sciences, 2022)
Exercise training is an essential component in the treatment or rehabilitation of various diseases and conditions. However, barriers to exercise such as the burdens of travel or time may hinder individuals’ ability to participate in such training programs. Advancements in technology have allowed for remote, home-based exercise training to be utilized as a supplement or replacement to conventional exercise training programs. Individuals in these home-based exercise programs are able to do so under varying levels of supervision from trained professionals, with some programs having direct supervision, and others having little to no supervision at all. The purpose of this review is to examine the use of home-based, tele-exercise training programs for the treatment of different disease states and conditions, and how these programs compare to conventional clinic-based exercise training programs.